TiO2/SWCNts: Linear and Nonlinear Optical Studies for Environmental Applications - Saloua Helali (C)
A series of single-walled carbon nanotube/titanium dioxide (SWCNTs/TiO2) composites were prepared by the incorporation of various concentrations (0, 5, 10, 20 V.%) of SWCNTs in TiO2. The prepared solutions were successfully formed on silicon and quartz substrates using the sol–gel spin-coating approach at 600 °C in ambient air. The X-ray diffraction method was used to investigate the structure of the samples. The absorbance and transmittance data of the samples were measured using a UV–vis spectrophotometer. Through the analysis of these data, both the linear and nonlinear optical properties of the samples were examined. Wemple–DiDomenico’s single-oscillator model was used to calculate the single-oscillator energy and dispersion energy. Finally, all samples’ photocatalytic performance was studied by the photodegradation of methylene blue (MB) in an aqueous solution under UV irradiation. It is found that the photocatalytic efficiency increases when increasing the SWCNT content. This research offers a new perspective for the creation of new photocatalysts for environmental applications.